The police in a free society: safeguarding rights while enforcing the law - Douglas, Todd (Praeger, 2017)
The paradox of policing a free society -- The evolution of the modern police force -- From neighborhood patrolman to law-enforcement officer -- The consequences of eroding respect -- The police and racial conflict in America -- The police as the face of the law -- Training the police for service instead of enforcement -- Police legitimacy and public relations -- Handling officers who abuse the public trust -- The police force the public deserves